Effects of oregano extract on oxidative, microbiological and sensory stability of sheep burgers packed in modified atmosphere. (May 2016) - Fernandes, R.P.P.; Trindade, M.A.; Lorenzo, J.M.; Munekata, P.E.S.; de Melo, M.P.
Abstract: The aim of this study was to evaluate the effects of oregano natural extract added to sheep burgers packaged in a modified atmosphere for 20 days at 2 ± 1 °C, seeking antioxidant properties and healthiness appeal. Antioxidant capacity of the oregano extract was determined by Folin-Ciocalteau, DPPH and FRAP methods. Three treatments of burgers were prepared: without antioxidant (control, CO), with 50 ppm BHT and with 1000 ppm oregano extract (ORE). The proximate composition (moisture, fat, protein and ash) of the meat product was determined and its stability was assessed through physicochemical (pH value, colour, lipid and protein oxidation, free fatty acids and volatile compounds profile), microbiological [total viable counts (TVC), Pseudomonas spp., Enterobacteriaceae, lactic acid bacteria (LAB)] and sensory analysis (5-point rating scale). ORE treatment presented similar counts of TVC and LAB and, also, an equivalent capacity to slow lipid and protein oxidation after 20 days, in comparison to BHT. The total amount of volatile compounds increased during storage ( P < 0.01) and all treatments showed a decrease ( P < 0.001) on a* value. However, ΔE0–20 was higher ( P < 0.05) for CO treatment, indicating visual colour changes perceived by consumers. The presence of natural extract prevented the loss of sensory qualities in sheep burgers up to 15 days of storage, being that changes in off-odour were consistent with the microbial results that indicate burgers spoilage. In conclusion, oregano extract presented antioxidant effects quite similar to BHT and thus, can be considered a viable solution for the production of sheep burgers with a healthier appeal. Highlights: Healthiness appeal with addition of oregano natural extract in sheep burgers. Antioxidant potential of Origanum vulgare by Folin-Ciocalteau, DPPH and FRAP. ΔE0 – 20 was higher for CO treatment, indicating visual colour changes perceptible. Natural extract prevented the loss of sensory qualities up to 15 days of storage. Oregano extract presented antioxidant similar effects in relation to BHT.